Epidemiological and spatial profile of acquired syphilis: a sectional study based on a historical series (Research, Society and Development, 2022)
Despite being preventable and curable, syphilis is a serious public health problem worldwide. This study seeks to describe the epidemiological and spatial profile of syphilis acquired in the North of Minas Gerais in the years 2016 to 2020. It is a cross-sectional, retrospective and descriptive study. Data collection was carried out using secondary data extracted from the Notification Diseases Information System (SINAN). A descriptive analysis of the variables was performed to characterize the epidemiological profile by checking frequency and percentage. Fisher's exact statistical test was applied to verify the association of variables, assuming a significance of 95% (p